Jurnal Penyuluhan: Efek Strategi Komunikasi Pemasaran Personal Selling PT Agricon Pada Petani Padi di Kabupaten Karawang - Nindya Ayu Wradsari, Anna Fatchiya (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2014)
The objective of this research was to determine the personal selling of marketing communication strategy which was conducted by PT Agricon and to examine the factors related to the effects of it. This research applies simple random sampling which was conducted by using quantitative methods and supported by qualitative approach.